Spread of Khorezm Oasis land mollusks in biotopes - Avazmetova Intizor Rajapboevna; Matyakubova Yulduzkhan Amanbayevna; Yadgarova Nazokat Saparbayena (Zien Journals, 2023)
Khorezm oasis, located in the north-western part of Uzbekistan, consists mainly of plains. This area is intended for irrigated agriculture-gardens, alfalfa plantations, vegetables, sugarcane crops, cotton and other technical crops. The research was conducted in 2020-2023. Study of distribution and morphological features of land molluscs, collection of shell molluscs A.A. Shileyko, and the collection of slime worms by I.M. Likharev and A.Y. Made in Victor styles. According to the results of the research, 14 species of land molluscs were found in 3 biotopes in the flat part of the research area, and common species were Xeropicta candacharica (in the 2nd biotope), C, nitens, V. costata, P. muscorum, Deroceras laeve (in the 3rd biotope), X. candacharica was considered the dominant species, its maximum density in the population was 100-110, and the average density was equal to 93.3
Keywords: Terrestrial mollusk; biotope; species; population